FAIR REDISTRIBUTION IN FINANCIAL MARKETS: A GAME THEORY COMPLETE ANALYSIS - Carfì, David; Musolino, Francesco (Journal of Advanced Studies in Finance; Vol 2 No 2 (2011): JASF Volume II Issue 2(4) Winter 2011, 2011)
The aim of this paper is to propose a methodology to stabilize the financial markets using Game Theory and in particular the Complete Study of a Differentiable Game, introduced in the literature by David Carfì. Specifically, we will focus on two economic operators: a real economic subject and a financial institute (a bank, for example) with a big economic availability. For this purpose we will discuss about an interaction between the two above economic subjects: the Enterprise, our first player, and the Financial Institute, our second player. The only solution which allows both players to win something, and therefore the only one desirable, is represented by an agreement between the two subjects: the Enterprise artificially causes an inconsistency between spot and future markets, and the Financial Institute, who was unable to make arbitrages alone, because of the introduction by the normative authority of a tax on economic transactions (that we propose to stabilize the financial market, in order to protect it from speculations), takes the opportunity to win the maximum possible collective (social) sum, which later will be divided with the Enterprise by contract.